Human language technology and communicative disabilities: requirements and possibilities for the future - Ruiter, Marina B.; Beijer, Lilian J.; Cucchiarini, Catia; Krahmer, Emiel J.; Rietveld, Toni C.M.; Strik, Helmer; Van hamme, Hugo (Language Resources and Evaluation, 2012)
For some years now, the Nederlandse Taalunie (Dutch Language Union) has been active in promoting the development of human language technology (HLT) applications for speakers of Dutch with communicative disabilities. The reason is that HLT products and services may enable them to improve their communication skills and verbal autonomy. We sought to identify a minimum common set of HLT resources that is required to develop tools for a wide range of communication disabilities. In order to reach this goal, we investigated the specific needs of communicatively disabled people and related these needs to the underlying HLT software components. By analysing the availability and quality of these essential HLT resources, we were able to identify which of the crucial elements need further research and development to become usable for developing applications for communicatively disabled speakers of Dutch. The results obtained in the current survey can be used to inform policy institutions on how they can stimulate the development of HLT resources for this target group. In the current survey results were obtained for Dutch, but a similar approach can also be applied to other languages.